TINDAK PIDANA TANPA KORBAN DI INDONESIA PENGATURAN DAN PROBLEMATIKANYA - Duwi Handoko (Menara Ilmu, 2018)
The term of victimless crime in positive criminal law in Indonesia is contained in only one law, namelyLaw Number 11 Year 2012 on the Criminal Justice System of the Child. Although in the law, the term"criminal act" without a victim is found, but there is no definition about that. Some of the behaviorscategorized as victimless crime are drunks, vagrants, gambling, prostitution, and drug use.Related to the pattern of setting up the crime without victims in Indonesia, the following conclusions areobtained: abortion, homosexuality and gambling are regulated in and outside the Criminal Code, vagrantsare only regulated in the Criminal Code, drug dependence is only regulated outside the Criminal Code, andnot rules for perpetrators and prostitution services, whether administered within or outside the CriminalCode.The problem of law enforcement on non-victim crimes in Indonesia is: abortion is not just about legalmatters. Therefore, international human rights bodies seek to avoid the issue of abortion. The prohibition ofmuddle life is a matter unrelated to the obligation of the state to care for the poor and neglected children.The problem of drug dependence is caused by the existence of "double standard" in the framework of lawenforcement which clearly and firmly arranged in Article 121 and Article 127 of Law Number 35 Year 2009about Narcotics. The problematic of prostitution is that there is no negative impact (punishment) forperpetrators and users of prostitution services. The problem of gambling is that the Criminal Code does notprohibit gambling activities. So, it is true that he is called a crime, but not forbidden, and instead givenpermission.Keywords: Victimless Crime, Prostitution, Abortion, Gambling